2020
DOI: 10.1038/s41598-020-74668-8
|View full text |Cite
|
Sign up to set email alerts
|

Automatic evaluation of degree of cleanliness in capsule endoscopy based on a novel CNN architecture

Abstract: Capsule endoscopy (CE) is a widely used, minimally invasive alternative to traditional endoscopy that allows visualisation of the entire small intestine. Patient preparation can help to obtain a cleaner intestine and thus better visibility in the resulting videos. However, studies on the most effective preparation method are conflicting due to the absence of objective, automatic cleanliness evaluation methods. In this work, we aim to provide such a method capable of presenting results on an intuitive scale, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Reinier Noorda et al adopted an automatic evaluation system of capsule endoscopy cleanliness based on a new CNN architecture. By dividing the gastrointestinal tract cleanliness into four grades (poor, general, good, and excellent), the objective and automatic cleanliness evaluation were realized, and a good classification accuracy (95.23%) was achieved [52]. On the field of cleanliness assessment of small-bowel capsule endoscopy, Romain Leenhardt et al also reported an accuracy of 89.7% to determine whether the bowel preparation is enough or not [53].…”
Section: Discussionmentioning
confidence: 99%
“…Reinier Noorda et al adopted an automatic evaluation system of capsule endoscopy cleanliness based on a new CNN architecture. By dividing the gastrointestinal tract cleanliness into four grades (poor, general, good, and excellent), the objective and automatic cleanliness evaluation were realized, and a good classification accuracy (95.23%) was achieved [52]. On the field of cleanliness assessment of small-bowel capsule endoscopy, Romain Leenhardt et al also reported an accuracy of 89.7% to determine whether the bowel preparation is enough or not [53].…”
Section: Discussionmentioning
confidence: 99%
“…Bowel cleanliness is a crucial point and different scales are now adopted for colonoscopy. In the context of SBCE, two most recent AI‐based algorithms have been proposed 34,35 . Both showed that AI can lead to a robust and reliable cleanliness metric at image level.…”
Section: Assessment Of Bowel Cleanlinessmentioning
confidence: 99%
“…In the context of SBCE, two most recent AI-based algorithms have been proposed. 34,35 Both showed that AI can lead to a robust and reliable cleanliness metric at image level. A recent contribution shows that the principle of DL approaches can be extended to the video level.…”
Section: Assessment Of Bowel Cleanlinessmentioning
confidence: 99%
“…To assess for quality of bowel preparation during VCE Leenhardt et al [ 159 ] and Noorda et al [ 160 ] developed a DL models based on CNN. Both models achieved accuracy of over 95%, with sensitivity and specificity of 94.7%-96.18% and 94.0%-94.33%, respectively.…”
Section: Lower Gastrointestinal Tractmentioning
confidence: 99%